Influence of saliva contamination on the shear bond strength of adhesives on enamel - Tatiana Feres Assad-Loss (Dental Press Journal of Orthodontics, 2012)
OBJECTIVE: To evaluate shear bond strength of 3 adhesive systems (Single Bond, TransbondTM MIP and TransbondTM XT) applied on bovine enamel under saliva contamination condition. METHOD: One hundred and twenty enamel surfaces of bovine incisors were divided into 6 groups (n = 20) according to the adhesive system used (TransbondTM XT, TransbondTM MIP and Single Bond) with or without saliva contamination. For each adhesive system, there were two groups defined as no contamination group (NC): 37% H3PO4 conditioning for 30 seconds and two layers of adhesive systems; saliva contamination group (SC): After the first adhesive layer application, the examined areas were contaminated with saliva. Samples were mounted appropriately for testing and stored in deionized water at 37 ºC for 7 days. Samples were then submitted to shear bond strength trials at a speed of 0.5 mm/min. The Adhesive Remnant Index (ARI) was evaluated under stereomicroscopy. Two-way analysis of variance and the Tukey test were used to compare mean values (α = 0.05). RESULTS: Groups XT (NC) = 26.29 ± 7.23; MIP (NC) = 24.47 ± 7.52 and SB (NC) = 32.36 ± 4.14 XT (SC) = 19.59 ± 6.76; MIP (SC) = 18.08 ± 6.39 and SB (SC) = 18.18 ± 7.03 MPa. ARI 0 and 1 were the most prevalent scores in all study groups examined. CONCLUSION: Saliva contamination significantly decreased bond strength of the three adhesive systems examined (p <0.05). However, the comparison of groups with and without saliva contamination did not reveal any significant differences, and, therefore, the three systems may be considered equivalent.